P=q/r
* * * * *
The correct answer is P = k*q/r where k is the constant of proportionality.
q = k*r^3/(s*sqrt(t))
If P varies directly with q, r and s then P = kqrs, where k is a constant. As 70 = k x 7 x 5 x 4 = 140k : k = 70/140 = 1/2 The equation of joint variation is P = ½qrs.
q + p
If p then q is represented as p -> q Negation of "if p then q" is represented as ~(p -> q)
p-q
If P varies directly with the square of Q then the equation would be in the form of P = kQ2, where k is the constant of variation so the new equation would be: P = 6Q2, so when Q = 12 we have P=6*122, or P = 864
q = k*r^3/(s*sqrt(t))
If P varies directly with q, r and s then P = kqrs, where k is a constant. As 70 = k x 7 x 5 x 4 = 140k : k = 70/140 = 1/2 The equation of joint variation is P = ½qrs.
Converse: If p r then p q and q rContrapositive: If not p r then not (p q and q r) = If not p r then not p q or not q r Inverse: If not p q and q r then not p r = If not p q or not q r then not p r
The sum of p and q means (p+q). The difference of p and q means (p-q).
Not sure I can do a table here but: P True, Q True then P -> Q True P True, Q False then P -> Q False P False, Q True then P -> Q True P False, Q False then P -> Q True It is the same as not(P) OR Q
q + p
If p = 50 of q then q is 2% of p.
If p then q is represented as p -> q Negation of "if p then q" is represented as ~(p -> q)
p-q
P! / q!(p-q)!
The assertion in the question is not always true. Multiplying (or dividing) 0 by a negative number does not yields 0, not a negative answer.Leaving that blunder aside, let p and q be positive numbers so that p*q is a positive number.Thenp*q + p*(-q) = p*[q + (-q)] = p*[q - q] = p*0 = 0that is p*q + p*(-q) = 0Thus p*(-q) is the additive opposite of p*q, and so, since p*q is positive, p*(-q) must be negative.A similar argument works for division.